Population pharmacokinetics of liposomal irinotecan in patients with cancer and exposure–safety analyses in patients with metastatic pancreatic cancer - Karl Brendel; Tanios Bekaii‐Saab; Patrick M Boland; Farshid Dayyani; Andrew Dean; Teresa Macarulla; Fiona Maxwell; Kabir Mody; Anna Pedret‐Dunn; Zev A Wainberg; Bin Zhang (CPT: Pharmacometrics & Systems Pharmacology, 2021)
Abstract Liposomal irinotecan is a liposomal formulation of irinotecan, which prolongs circulation of irinotecan and its active metabolite SN‐38. A population pharmacokinetic (PK) model was developed based on data from seven studies (N = 440). Adequacy of the model was assessed using multiple methods, including visual predictive check. Associations between PK exposure and the incidence of diarrhea (grade ≥3) and neutropenia adverse events (AEs) (grade ≥3) at first event in patients with metastatic pancreatic ductal adenocarcinoma (mPDAC) were investigated using logistic regression based on data from two studies (the phase III NAPOLI‐1 [N = 260] and phase I/II NCT02551991 [N = 56] trials). The PKs of total irinotecan was described by a two‐compartment model with first‐order elimination, with SN‐38 formed directly by a first‐order constant from the central compartment of irinotecan or after using a transit compartment. Clearance was 17.9 L/week (0.107 L/h) and 19,800 L/week (118 L/h) for total irinotecan and SN‐38, respectively. The UGT1A1*28 7/7 homozygous genotype had no significant impact on SN‐38 clearance. Model evaluation was satisfactory for both irinotecan and SN‐38. The incidence of diarrhea (grade ≥3) at first event was significantly higher with increasing average concentrations of total irinotecan and SN‐38; there was no significant association between an increased risk of neutropenia AEs (grade ≥3) at first event and average SN‐38 concentrations. In summary, the PKs of total irinotecan and SN‐38 after administration of liposomal irinotecan were well‐described by the model. The UGT1A1*28 status had no significant impact on the PKs of liposomal irinotecan.